Dynamic transition of transcription and chromatin landscape during fission yeast adaptation to glucose starvation. (2nd March 2015) - Oda, Arisa; Takemata, Naomichi; Hirata, Yoshito; Miyoshi, Tomoichiro; Suzuki, Yutaka; Sugano, Sumio; Ohta, Kunihiro
<x xml:space="preserve">Abstract</x> Shortage of glucose, the primary energy source for all organisms, is one of the most critical stresses influencing cell viability. Glucose starvation promptly induces changes in mRNA and noncoding RNA (ncRNA) transcription. We previously reported that glucose starvation induces long ncRNA (lncRNA) transcription in the 5′ segment of a fission yeast gluconeogenesis gene (fbp1+), which leads to stepwise chromatin alteration around the fbp1+ promoter and to subsequent robust gene activation. Here, we analyzed genomewide transcription by strand‐specific RNA sequencing, together with chromatin landscape by immunoprecipitation sequencing (ChIP‐seq). Clustering analysis showed that distinct mRNAs and ncRNAs are induced at the early, middle and later stages of cellular response to glucose starvation. The starvation‐induced transcription depends substantially on the stress‐responsive transcription factor Atf1. Using a new computer program that examines dynamic changes in expression patterns, we identified ncRNAs with similar behavior to the fbp1+ lncRNA. We confirmed that there are continuous lncRNAs associated with local reduction of histone density. Overlapping with the regions for transcription of these lncRNAs, antisense RNAs are antagonistically transcribed under glucose‐rich conditions. These results suggest that Atf1‐dependent integrated networks of mRNA and lncRNA govern drastic changes in cell physiology in response to glucose starvation.